Simple and Rapid Quantification of Thrombocytes in Zebrafish Larvae - Huarng, Michael C. (Zebrafish, 2015)
Platelets are a critical component of hemostasis, with disorders of number or function resulting in coagulation disturbances. Insights into these processes have primarily been realized through studies using mammalian models or tissues. Increasingly, zebrafish embryos and larvae have been used to study the protein and cellular components of hemostasis and thrombosis, including the thrombocyte, a nucleated platelet analog. However, investigations of thrombocytes have been somewhat limited due to lack of a robust and simple methodology for quantitation, an important component of platelet studies in mammals. Using video capture, we have devised an assay that produces a rapid, reproducible, and precise measurement of thrombocyte number in zebrafish larvae by counting fluorescently tagged cells. Averaging 1000 frames, we were able to subtract background fluorescence, thus limiting assessment to circulating thrombocytes. This method facilitated rapid assessment of relative thrombocyte counts in a population of 372 zebrafish larvae by a single operator in less than 3 days. This technique requires basic microscopy equipment and rudimentary programming, lends itself to high throughput analysis, and will enhance future studies of thrombopoiesis in the zebrafish.